2019
DOI: 10.1002/pssb.201900478
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Properties of Eu3+ Ions in Sol–Gel Materials Containing Calcium Fluoride Nanocrystals

Abstract: In this study, a series of Eu3+‐doped silicate xerogels with modified initial compositions is prepared and heat treated at 350 °C to fabricate glass‐ceramic materials containing CaF2 nanocrystals. The impact of an N,N‐dimethylformamide (DMF) additive and a catalyst agent (CH3COOH, HNO3) on the sol–gel transformation from liquid sols through silicate gels and xerogels into glass‐ceramics is investigated using infrared spectroscopy. To verify the formation of CaF2 nanocrystals, X‐ray diffraction (XRD) measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…Therefore, the results indicate the evaporation of organic components and water molecules in dry gels and the progressive polycondensation reaction of silicate networks during the glass transition process [31]. Moreover, the broad absorption band of CBS glass located at ~1100 cm −1 corresponding to [BO 4 ] is more intense than that of dry gels, while the broad absorption band assigned to [BO 3 ] of CBS glass at ~1440 cm −1 is weaker than that of dry gels [21,25,31]. It can be concluded that a large number of [BO 3 ] functional groups are transformed into [BO 4 ] functional groups during the glass transition process.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…Therefore, the results indicate the evaporation of organic components and water molecules in dry gels and the progressive polycondensation reaction of silicate networks during the glass transition process [31]. Moreover, the broad absorption band of CBS glass located at ~1100 cm −1 corresponding to [BO 4 ] is more intense than that of dry gels, while the broad absorption band assigned to [BO 3 ] of CBS glass at ~1440 cm −1 is weaker than that of dry gels [21,25,31]. It can be concluded that a large number of [BO 3 ] functional groups are transformed into [BO 4 ] functional groups during the glass transition process.…”
Section: Resultsmentioning
confidence: 87%
“…In addition, the intensities of the three absorption bands decrease significantly after the glass transition process. Therefore, the results indicate the evaporation of organic components and water molecules in dry gels and the progressive polycondensation reaction of silicate networks during the glass transition process [31]. Moreover, the broad absorption band of CBS glass located at ~1100 cm −1 corresponding to [BO 4 ] is more intense than that of dry gels, while the broad absorption band assigned to [BO 3 ] of CBS glass at ~1440 cm −1 is weaker than that of dry gels [21,25,31].…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The series of xerogels co-doped with Tb 3+ and Eu 3+ ions were synthesized using the sol-gel method described elsewhere [ 41 , 46 ]. All reagents were taken from Sigma Aldrich Chemical Company (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%